EXPERIENCE OF APPLYING MONOCLONAL ANTIBODIES TO TNF α — ADALIMUMAB — IN A CHILD WITH JUVENILE IDIOPATHIC ARTHRITIS - E. I. Alexeeva; K. B. Isaeva; R. V. Denisova; T. V. Sleptsova; S. I. Valiyeva; T. M. Bzarova; E. V. Mitenko; A. M. Chomakhidze (Педиатрическая фармакология)
The article offers successful application of a preparation of human monoclonal antibodies to tumor necrosis factor (TNF) α – adalimumab – in the setting of a severe course of juvenile idiopathic arthritis characterized by inefficiency of the standard antirheumatic therapy and secondary resistance to chimeric antibodies to TNF α. Adalimumab treatment secured overcoming of the secondary infliximab inefficiency, rapid disease activity decrease, peripheral joints’ function recovery and the patient’s functional activity increase in a short space of time. The drug averted the patient’s steadily progressing incapacitation and induced the clinical-laboratory disease remission development.